An Examination of the Impacts of Gender, Race, and Ethnicity on the Judicial Processing of Offenders in Family Violence Cases. (December 2018) - Freiburger, Tina L.; Romain, Danielle
Using the focal concerns perspective, the present study examined possible gender, race, and ethnic disparities on judges' pretrial release, incarceration, and sentence length decisions in family violence cases. The results indicate that males were more likely to receive an order of bail (as opposed to release on own recognizance), received higher bail amounts, were less likely to make bail, were more likely to receive prison opposed to jail, and were incarcerated for significantly longer periods of time than women. Hispanic defendants were more likely than White defendants to receive higher bail amounts and were more likely to be detained until sentencing. Black defendants, on the other hand, were more likely to receive prison as opposed to jail than White offenders.